The Effect of Nurse Driven Protocol Implementation on the Incidents of Catheter Acquired Urinary Tract Infection in Geriatric Patients - Tiodora Tiodora; Junaiti Sahar; Kuntarti Kuntarti (GLOBAL HEALTH SCIENCE GROUP, 2025)
The aging process affects the immune system, making the elderly more vulnerable to bacterial and viral infections. Urinary tract infection (UTI) is the second most common infection among geriatric patients. UTIs caused by urinary catheter use, known as Catheter Acquired Urinary Tract Infections (CAUTI), are the leading cause of nosocomial infections, with 80% linked to catheter use. Preventing catheter use beyond 72 hours can reduce CAUTI incidence. The use of Nurse Driven Protocols (NDP) is one of the interventions recommended by the CDC to reduce catheter-related risk factors. This articles aiming to discuss the impact of NDP implementation on the incidence of CAUTI in geriatric patients. This study was conducted using the PRISMA checklist. Literature searches were conducted through several databases, including ProQuest. Science Direct, Scopus, and ClinicalKey Nursing, within the last five years (2020–2024). From 110 identified articles, five met the inclusion criteria, and two were analyzed in depth. The implementation of Nurse Driven Protocols (NDP) significantly reduced the incidence of CAUTI by ensuring catheters are only used when absolutely necessary and removed as soon as no longer indicated. Routine 24-hour assessments enable nurse to independently evaluate catheter use based on clear clinical criteri , such as the HOUDINI system. NDP empowers nurse to conduct independent evaluations and make decisions regarding catheter use, effectively preventing CAUTI and improving the quality of patient care.